Pío IX, la americanización de un pontífice: de la relación de Estado a la devoción popular - Cárdenas Ayala, Elisa (Revista Brasileira de História das Religiões, 2025)
This article proposes an approach to the way in which, throughout the nineteenth century, in the framework of the construction of direct relations between the nations detached from Spanish and Portuguese domination and the Catholic Church, the figure of the Roman pontiff, as head of the Catholic Church, was being "Americanized". This happened not only because of the interest and action of the governments and faithful of the region, interested in a rapprochement with the leader of the Roman Catholic Church, but also because of the direct participation of the pontiff in the construction of these relations both politically and religiously, at a time when both were considered inseparable from his perspective, vis a vis a world in which the differentiation between them was actively constructed.